Awareness of HPV and drivers of HPV vaccine uptake among university students in Italy. (13th November 2019) - Baldovin, T; Cocchio, S; Fonzo, M; Bennici, S E; Buja, A; Bertoncello, C; Baldo, V
Abstract: : HPV vaccination is a milestone in primary prevention. However in Italy, vaccine coverage is still nowhere near the target of 95%. We investigated drivers of vaccine uptake among university students, as they are likely to have just assumed a central role in their healthcare decision-making and potential barriers may differ from parents. University students aged 18-25 were asked to fill in a questionnaire. The effect of socio-demographic and behavioural characteristics on HPV awareness was assessed with a logistic regression adjusting for age, gender, nationality, degree course, relationship, age at first intercourse, number of sexual partners, smoking, sexual orientation, past diagnosis of STDs and knowledge of people who had received HPV vaccine. A second regression adjusting also for information sources, awareness and knowledge investigated drivers of vaccine uptake. 9, 988 questionnaires were included; awareness of HPV and vaccine was 83.3% and 69.9%, respectively. Awareness (adjOR: 3.3 95%CI 2.3-4.6) and a good knowledge positively affected acceptability, as well as a previous diagnosis of STDs and knowledge of vaccinated people. Healthcare workers (adjOR 1.6 95%CI 1.4-1.9) and family members (adjOR 1.7 95%CI 1.4-2.1) were the most influencing information sources, even if knowledge of vaccinated people was by far more persuasive (adjOR 2.7 95%CI 2.2-3.3). Only 12% of participants were acquainted with skin to skin HPV transmission, while 75% believed in a full effectiveness of condom; less than 22% associated HPV with cancer (other than cervical cancer). Efforts to increase awareness are likely to be worth considering that: awareness is the main determinant of vaccine uptake; only 50% of individuals not interested in receiving vaccine were aware of it; males are much less aware (adjOR 0.09 95%CI 0.07-0.11). Moreover, this study spotlights some misconceptions and may provide suitable evidence in tailoring more efficacious communication strategies. Key messages: There is room for improving the awareness of HPV. Efforts are likely to be worth since it remains the main determinant of vaccine uptake. Awareness has been growing but a gender gap still persists. Communication should focus more on HPV involvement in neoplasia other than cervical cancer; transmission via skin to skin contact; multiple sex partnership; partial protection of condom.